Morphometric parameters of the relief and drainage network of the Formiga River subbasin, Minas Gerais, Brazil - Reis , Igor Luís; Marinho, Gustavo Sousa; Rios, Guilherme da Silva; Santana, Derielsen Brandão; Lense, Guilherme Henrique Expedito; Mincato, Ronaldo Luiz; Rubira, Felipe Gomes (Revista Brasileira de Geomorfologia, 2023)
This research analyzed the morphological/morphometric parameters of the relief and drainage network of the Formiga River subbasin, southern Minas Gerais State, Brazil, aiming at identification and the exam the influences of control mechanisms in the development of current configurations. The methodology was based on the application of indices and parameters: (1) slope length (Hack's Sl); (2) normalized slope index (Ksn); (3) river hierarchy; (4) drainage density; (5) hydrographic density; (6) sinuosity index; (7) density of structural lineaments; (8) transverse topographic symmetry factor; (9) asymmetry factor of drainage basins; (10) topographic profiles transverse to the valleys; (11) relief ratio; (12) roughness index; (13) roughness concentration index; (14) compactness coefficient; (15) circularity index; and (16) form factor. The results indicated three sectors with distinct geomorphic behaviors, which resulted in peculiar surface structures and divergent current dynamics. The Formiga River subbasin presents physical evidence that demonstrates and corroborates with the structural control in the development of the current drainage network and relief. The construction of dams affected the dynamics of the lower course of the river, drowned by the reservoir of the hydroelectric plant of Furnas.